On the Basic Principles of Civil Law Applicable Boundaries in Judicial Judgments - Zhang, Guoqi (International Journal of Social Sciences and Public Administration, 2025)
As the core guidelines that run through the entire civil legislation and judicial practice, the basic principles of civil law are of great significance in judicial adjudication. This article aims to explore the applicable conditions, restrictions and relationships between the basic principles of civil law in judicial judgments and other legal norms. By analyzing the function and value of the basic principles of civil law in legislation, justice and practice, this article believes that the basic principles of civil law should be used as an important benchmark to supplement legal loopholes and equitable case justice in judicial adjudication, but at the same time, they are subject to the statutory framework. When applying the basic principles of civil law, judges should fully consider the actual situation of the case, combine the spirit of law and policies, and ensure the fairness and reasonableness of the judgment results.The research of this article is to improve China's civil legal system.As well asIt is of practical significance to guide judicial practice.